Literature review on shot peening simulation. (1st November 2010) - Zimmermann, Marc; Klemenz, Manuel; Schulze, Volker
Simulation models describing the fundamental processes taking place during a shot peening treatment are being proposed since the last four decades in order to investigate, understand, explain and predict the correlation between the influencing factors of shot peening and the process results. This article provides a broad and extensive literature survey on simulation models of the shot peening process that have been developed and applied in the past decades and summarises the knowledge that has been gained.